Relationship between phytoplankton diversity and water quality of Bauluang Island in Takalar Regency, South Sulawesi - ANDI MARSAMBUANA PIRZAN; PETRUS RANI PONG-MASAK (Biodiversitas Journal of Biological Diversity, 2008)
Phytoplankton can be used as indicator of waters environment quality. This research was conducted in Bauluang Island waters of Takalar Regency of South Sulawesi. The aims of this research were study the richness and stabilization of Bauluang Island waters by analysis of phytoplankton diversity and their relationship of waters quality. Plankton net no. 25 was used to phytoplankton collection then it was preserved in MAF solution. Identification of phytoplankton was conducted until species level and counting cell method was used to calculate their population density. Varies phytoplankton density at the range of 470-2,680 ind./L and species at the range of 5-20 species. Phytoplankton stabilization was moderate while phytoplankton evenness was spread. Correlation (r) of phytoplankton diversity with alkalinity and total organic matter was 0.61 respectively.Â© 2008 Jurusan Biologi FMIPA UNS SurakartaKeywords: diversity, phytoplankton, water quality, Bauluang Island